(untitled) (Tikrit Journal of Veterinary Science, 2023)
The primary objective of this study was to enhance the therapeutic potential of conventional Lidocaine by encapsulating it within a phytosome derived from ordinary pumpkin seed oil. This modification was pursued with dual aims: to enhance the physical stability of the oil and to improve the therapeutic efficacy while minimizing the adverse effects typically associated with Lidocaine. To evaluate the therapeutic impact of Nano-phytosome pumpkin-lidocaine gel (referred to as Nano-Lidocaine) on the healing of third-degree burn wounds .A cohort of thirty adult rabbits, comprising both male and female individuals aged between 10 and 18 weeks, characterized by white fur and weighing between 2.5 to 3 kg, was utilized. These rabbits were stratified into five groups, each consisting of five subjects: Negative Control Group: This group received no treatment and served as the baseline control for comparison. Positive Control Group: In this group, rabbits were administered empty liposomes, serving as a control for the liposomal carrier without active ingredients. Ordinary Pumpkin Seed Oil Group: Rabbits in this group received treatment with ordinary pumpkin seed oil, serving as a reference for evaluating the therapeutic effects of the base oil. Nano-Lidocaine 100% Gel Group: Rabbits in this group were treated with Nano-Lidocaine gel at a concentration of 100%, containing both Lidocaine and pumpkin phytosomes. Nano-Phytosome Pumpkin 100% Gel Group: Rabbits in this group were treated with Nano-Phytosome pumpkin gel at a concentration of 100%, serving as a control for the carrier without Lidocaine. After a 30-day treatment period, it was observed that both Nano-Lidocaine gel (100%) and Nano-Phytosome pumpkin gel (100%) demonstrated significant wound contraction, with measurements of 0.235 cm and 0.274 cm, respectively. These results were in stark contrast to the ordinary pumpkin seed oil-treated group, as well as both the negative and positive control groups, which exhibited measurements of 0.313 cm, 0.313 cm, and 0.274 cm, respectively. In conclusion, the study successfully developed a Nano-Lidocaine formulation encapsulated within pumpkin phytosomes, which exhibited enhanced therapeutic effects in terms of wound healing. These findings suggest the potential utility of this novel formulation in clinical applications, particularly for the treatment of third-degree burn wounds.